Stakeholder-specific assessment of environmental, economic and social effects of resource-efficiency measures in urban districts - first results. Issue 5 (November 2020) - Volk, Rebekka; Lützkendorf, Thomas; Schambelon, Sophia; Naber, Elias; Mörmann, Kai; Böhnke, Denise; Norra, Stefan; Schuhmann, Rainer; Ehbrecht, Anke; Balouktsi, Maria; Schultmann, Frank
Abstract: There is a great interest in society in making urban districts more sustainable. Sustainable and resource-efficient urban development (SDG 11) is a process that, based on the analysis of the initial situation, leads to the formulation of specific goals and must be planned, accompanied, assessed and managed. Thus, this contribution presents a fundamental, multi-perspective concept to assess and manage the use of (natural) resources (stocks and flows), in particular (1) water (rain, potable and waste water), (2) land use (settlements, traffic area, open/green areas, ecosystems), (3) raw materials (material in- and outputs, recycling and disposal, C&D waste, and fossil fuels) in a defined urban district.